2007
DOI: 10.1038/ng2031
|View full text |Cite
|
Sign up to set email alerts
|

Modifiers of epigenetic reprogramming show paternal effects in the mouse

Abstract: There is increasing evidence that epigenetic information can be inherited across generations in mammals, despite extensive reprogramming both in the gametes and in the early developing embryo. One corollary to this is that disrupting the establishment of epigenetic state in the gametes of a parent, as a result of heterozygosity for mutations in genes involved in reprogramming, could affect the phenotype of offspring that do not inherit the mutant allele. Here we show that such effects do occur following patern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
149
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(158 citation statements)
references
References 49 publications
8
149
0
1
Order By: Relevance
“…Although histone modifications in paternal chromatin could be one contributing route (Hammoud et al 2009, Brykczynska et al 2010, information 'embossed' into the differential packaging of sperm chromatin also offers potential non-Mendelian traits the chance to influence zygotic phenotype. Evidence for an epigenetic influence driving such variation has been presented for both human (Pembrey et al 2006, Jirtle & Skinner 2007 and animal inheritance (Chong et al 2007). We speculate that the underlying framework for post-translational modifications including histone methylation is established by differential packaging of sperm chromatin, which the limited MNase digestion used in this and our related study (Arpanahi et al 2009) both reveals and exploits.…”
Section: 03mentioning
confidence: 52%
“…Although histone modifications in paternal chromatin could be one contributing route (Hammoud et al 2009, Brykczynska et al 2010, information 'embossed' into the differential packaging of sperm chromatin also offers potential non-Mendelian traits the chance to influence zygotic phenotype. Evidence for an epigenetic influence driving such variation has been presented for both human (Pembrey et al 2006, Jirtle & Skinner 2007 and animal inheritance (Chong et al 2007). We speculate that the underlying framework for post-translational modifications including histone methylation is established by differential packaging of sperm chromatin, which the limited MNase digestion used in this and our related study (Arpanahi et al 2009) both reveals and exploits.…”
Section: 03mentioning
confidence: 52%
“…Van der Heijden and his colleagues (2006) suggested that these histones, as well as methylated cytosines in centromeric DNA, are associated with the transgenerational maintenance of the structure of centromeric heterochromatin. Chong et al (2007) reported that when male mice had mutations in genes involved in epigenetic programming-in a gene that encodes a chromatin remodeler protein, and in another that encodes DNA methyltransferasethere were phenotypic effects on their offspring, even when they did not inherit the defective gene. Extensive epigenetic (methylation) variation has been found in human germ cells (Flanagan et al 2006), but whether and to what extent this variation is passed between generations is not known.…”
Section: Eiss and The Germlinementioning
confidence: 99%
“…(104) It has also been reported that modifiers of epigenetic reprogramming show paternal effects in mice. (111) Perhaps the most exciting aspect of this field, and one with the capacity to change our view of inheritance and evolution, (109) is the recently described phenomenon of 'paramutation'. Paramutation refers to the allele-specific transfer of epigenetic information to cause the heritable silencing of one allele by another and appears to involve RNA signalling in both maize and mice.…”
Section: Review Articlementioning
confidence: 99%